Semiotic Analysis of Cultural Branding Representation of Shopee Advertisements - Annisa Humaira; Nursapiah Harahap; Muhammad Diponegoro (Institute of Computer Science (IOCS), 2022)
The problem formulation explains how to analyze the semiotics of the cultural branding representation of shopee ads from the design display of 3 shopee advertisements for the last 3 months in 2020. The purpose of this study is to analyze the semiotics of cultural branding representation of shopee advertisements from the design display of 3 shopee advertisements for the last 3 months in 2020. This study it is useful to add to the study of the cultural representation of shopee advertising branding from the design display of 3 shopee advertisements for the last 3 months in 2020. This study uses a qualitative method of Roland Barthes semiotic analysis. Data collection techniques using observation and documentation methods. The results showed that the cultural representation of shopee advertising branding from each of the 3 design displays of Shopee ads, including Shopee 10.10 Brands Festival ads, 11.